3D imaging in medicine - Udupa, Jayaram K.; Herman, Gabor T. (CRC Press, 2000)
3D Imaging in Medicine, Second Edition provides a ready reference on the fundamental science of 3D imaging and its medical applications. It describes in tutorial fashion the principles and methods related to all aspects of 3D imaging, including image interpolation; filtering; segmentation; registration; isosurfacing; surface and volume rendering; quantitation; and evaluation of 3D imaging methods. KEY FEATURES: o Surveys clinical applications of 3D imaging currently pursued, including detailed information on computer integrated surgery, radiation therapy, CT angiography, orthopedics, and motion analysis of jointso Illustrates methods using software readily available on the Interneto Provides over 100 color images that effectively portray details, particularly for 3D renditions Catalog Copy .